The ranqueles’ letters of the nineteenth century: a corpus under construction (Quinto Sol, 2019)
The nineteenth century ranqueles letters contain a social story also shows fluctuations between confrontation and diplomacy, a profound interplay ethnic conflict and civil strife had in Argentina. This paper offers a summary of the letters ranqueles exchanged with different political, military and religious authorities between 1840 and 1879, located in two state archives and one religious. Reviewing our own travel research is the starting point for a review on the progress made in the declassification, constitution and study of this corpus which necessarily should be considered in dialogue with pieces written by the "Christian" partners the ranqueles.
Keywords: ranqueles; letters; frontier; conflict